1976
DOI: 10.1128/iai.14.5.1113-1118.1976
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of capsular type to biochemical and immunological properties of teichoic acid preparations from unencapsulated strains of Staphylococcus aureus

Abstract: We investigated the biochemical and immunological characteristics of teichoic acid preparations (TAP) obtained from four unencapsulated strains ofStaphylococcus aureus which nonetheless, according to the serum-soft agar technique, produced capsular type antigen and were representative of the four types A, B, C, and D. In the agar diffusion test, TAP of each strain produced a single precipitin line only against rabbit antisera corresponding to the homologous capsular type; no lines were observed against antiser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…These results matched the findings obtained by electronmicroscopy (Yoshida & Minegishi 1975). The relationship of capsular-type to biochemical and immunological properties of cell wall teichoic acid preparations reported by Ohtomo et al (1976) agree with these findings especially those obtained with unencapsulated strains. Concerning the population of encapsulated strains of Staph.…”
Section: Discussionsupporting
confidence: 89%
“…These results matched the findings obtained by electronmicroscopy (Yoshida & Minegishi 1975). The relationship of capsular-type to biochemical and immunological properties of cell wall teichoic acid preparations reported by Ohtomo et al (1976) agree with these findings especially those obtained with unencapsulated strains. Concerning the population of encapsulated strains of Staph.…”
Section: Discussionsupporting
confidence: 89%
“…Kelly and Weed (11) and Liau et al (13) found taurine to be a unique constituent of the cell wall or cell surface of the microorganisms. However, no one has observed the presence of taurine in the cell wall of S. aureus (23). We have shown that a crude enzyme preparation of cysteic acid decarboxylase can catalyze the formation of taurine in vitro.…”
Section: Discussionmentioning
confidence: 80%
“…Adhesion with soybean lectin, in particular, is likely to be affected by changes in the receptor because of cellular damage on the cell surface polysaccharide (14,35). It is known that the unencapsulated strain does not contain N-acetylgalactosamine in the cell surface fraction (14,19). Also, the ability of the encapsulated strain S-7 to adhere to fibrinogen increased after freeze-drying treatment.…”
Section: Discussionmentioning
confidence: 99%